Interdisciplinary approach for the management of bilaterally impacted maxillary canines - Sukh, Ram (Contemp Clin Dent, 2014)
Interdisciplinary approach for the management of malocclusion provides a holistic approach of patient management. Prudent treatment planning is necessary to achieve the various treatment goals. This case report describes the orthodontic management of a 16-year-old adolescent female patient with bilateral labially impacted maxillary canines. The problems associated with impacted maxillary canines and the biomechanical interventions used for this patient are discussed. The treatment protocol involved surgical intervention, followed by sequential traction of the impacted teeth. An interdisciplinary approach to treatment with different mechanical strategies led to the achievement of the desired esthetic, functional, and occlusal treatment goals.